Pengaruh Total Quality Management Terhadap Daya Saing Pada Hotel Aston Manado - Siwu, Audrey; Palandeng, Indrie Debbie; Karuntu, Merlyn Mourah (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
Total Quality Management (TQM) is a managerial approach that focuses on improving quality in all aspects of operations. It emphasizes the importance of customer satisfaction, continuous improvement, and the development of a culture of quality within the organization. By integrating TQM principles, Hotel Aston Manado can optimize services, improve operational efficiency, and build better relationships with customers. This study aims to examine three independent variables, namely Customer Focus (X1), Obsession with Quality (X2), and Continuous System Improvement (X3) on the dependent variable, namely Competitiveness (Y). This study uses a quantitative approach method with sampling techniques using purposive sampling. Data collection in this study used a questionnaire with Likert scale measurements. The questionnaire was distributed to 50 respondents of Aston Manado Hotel employees. The data processing model in this study uses multiple linear regression with SPSS version 30 software as a statistical tool. The results of the analysis show that simultaneously Focus on Customers (X1), Obsession with Quality (X2), and Continuous System Improvement (X3) have a significant effect on competitiveness, with an Fcount value of 24.916> Ftable 2.012. Partial test results also revealed that Focus on Customers (X1) with a Thitung of 3.953 > Ttable 2.012, Obsession with Quality (X2) with a Thitung of 2.206, > Ttable 2.012, and Continuous System Improvement (X3) Thitung of 3.272 < Ttable 2.012 had a positive and significant effect Kata Kunci: TQM, Fokus Pada Pelanggan, Obsesi Terhadap Kualitas, Perbaikan Sistem, Daya Saing.